EPIDEMIOLOGY OF COMPLICATION DEVELOPMENT IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Type 2 diabetes mellitus represents a major global public health burden due to its rapidly increasing prevalence and strong association with a wide spectrum of chronic complications. This study aims to analyze the epidemiological patterns of complication development in patients with type 2 diabetes mellitus, with particular emphasis on cardiovascular, cerebrovascular, renal, and metabolic outcomes. The analysis is based on population-based epidemiological data, clinical registries, and observational studies evaluating the incidence, prevalence, and risk factors of diabetes-related complications. The findings demonstrate that the risk of both macrovascular and microvascular complications increases significantly with disease duration, poor glycemic control, and the presence of concomitant metabolic disorders. Cardiovascular complications remain the leading cause of morbidity and mortality among patients with type 2 diabetes, while diabetic nephropathy and neuropathy represent major contributors to long-term disability. The epidemiological evidence indicates that complications often develop subclinically and progress over time, underscoring the importance of early detection and continuous surveillance. These results highlight the critical role of epidemiological assessment in understanding complication dynamics and support the implementation of population-based prevention strategies to reduce the burden of type 2 diabetes mellitus and its complications.
Keywords: Type 2 diabetes mellitus; epidemiology; diabetic complications; cardiovascular disease; microvascular complications; disease burden